Analysis of Potential Risks and Work Accidents Using Hazard Identification, Risk Assessment and Risk Control (HIRARC) Method: a Warehouse Support Case Study of PT. Vale Indonesia Tbk - Palengka, Greyfi Juita; Inca Liperda, Rahmad (Jurnal Logistik Indonesia, 2022)
Occupational Safety and Health (OSH) aims to maintain and improve the health and safety of the employees. Low levels of workplace safety may result in significant effects on the health of the employees. This research intends to use the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) technique to identify the likely hazards and assess the potential accident or financial loss that the company could incur. A case study of the warehouse of PT Vale Indonesia Tbk, one of the leading mining companies in Indonesia, is used to evaluate the effectiveness of the method. The results show that there are multiple classifications of the level of risk that can be encountered in the warehouse’s operational activities, including extreme, high, moderate and low level. Ultimately, this research proposes a series of improvement recommendations to minimize the occurrence of risks and hazards.